Advanced radiological work-up as an adjunct to decision in early reconstructive surgery in brachial plexus injuries - Abul-Kasim, Kasim; Backman, Clas; Björkman, Anders; Dahlin, Lars B (Journal of Brachial Plexus and Peripheral Nerve Injury, 2010)
Background As neurophysiologic tests may not reveal the extent of brachial plexus injury at the early stage, the role of early radiological work-up has become increasingly important. The aim of the study was to evaluate the concordance between the radiological and clinical findings with the intraoperative findings in adult patients with brachial plexus injuries.Methods Seven consecutive male patients (median age 33; range 15-61) with brachial plexus injuries, caused by motor cycle accidents in 5/7 patients, who underwent extensive radiological work-up with magnetic resonance imaging (MRI), computed tomography myelography (CT-M) or both were included in this retrospective study. A total of 34 spinal nerve roots were evaluated by neuroradiologists at two different occasions. The degree of agreement between the radiological findings of every individual nerve root and the intraoperative findings was estimated by calculation of kappa coefficient (К-value). Using the operative findings as a gold standard, the accuracy, sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of the clinical findings and the radiological findings were estimated.Results The diagnostic accuracy of radiological findings was 88% compared with 65% for the clinical findings. The concordance between the radiological findings and the intraoperative findings was substantial (К = 0.76) compared with only fair (К = 0.34) for the clinical findings. There were two false positive and two false negative radiological findings (sensitivity and PPV of 0.90; specificity and NPV of 0.87).Conclusions The advanced optimized radiological work-up used showed high reliability and substantial agreement with the intraoperative findings in adult patients with brachial plexus injury.